Entrepreneurship, Knowledge, Innovation and Sustainable Development - Kruja, Alba (Mediterranean Journal of Social Sciences, 2012)
Entrepreneurship is closely affiliated to knowledge, innovation and flexibility, factors that are directly related to competitivenessin the globalized economy. Obtaining prosperity in the globalized and liberalized world economy is related to the competitiveness degreeof the country. Being competitive in the international markets by fostering entrepreneurship has become a primary concern of policymakers in the developed and developing countries too, which are trying to attain their competitiveness. For an economy to developsustainable and shared increases in per capita income are needed. The increases in per capita income should be accompanied bymovements of the economy`s structural composition towards higher value added goods and more efficient production methods.Entrepreneurs can contribute to the economy through the allocation of resources in a more productive way, by giving support to changesin structures, by making discoveries in order to lower costs, increase efficiency, produce in a more effective way. The aim of this paper isto examine the recent advances in the understanding the relationship between knowledge, entrepreneurship and innovation in one hand,and how they relate to the sustainable development on the other. The methods of research are analysis and synthesis of the scientificliterature discussing how entrepreneurship can contribute to the economy and society and how can it be fostered through knowledge andinnovation.